Fluxo de metano na atmosfera sobre uma cultura de arroz irrigado por inundação no sul do Brasil - Maboni, Cristiano (2016)
The rice paddy is responsible for 12-16% of the anthropogenic emission of CH4 in the world. Brazil is one of most important rice paddy producer. The goal of this study is to understand the dynamics of methane exchange between rice paddy and the atmosphere in the south of Brazil. Two estimation techniques are used: eddy covariance and soil chamber. Data were obtained in a rice paddy farm in Cachoeira do Sul municipality. The total emission of methane in 2015-2016 rice paddy growing season (November 14, 2015 to April 16 2016) was 35.7 gCH4m−2. The solar radiation is the weather forcing that showed a higher correlation with methane emissions.